Militarization of the Arctic Ocean. - Weander, Nathaniel A. (Fort Leavenworth, KS : US Army Command and General Staff College, 2020)
The physical conditions in the Arctic are changing. The Arctic ice pack dominated the Arctic Ocean for most of mankind's history. In the last few decades, it has retreated to the point two new sea lines of communication have emerged. Military planners will need to prepare differently whether they expect these sea lines of communication to become militarized or whether they will become zones of cooperation. This monograph examines what conditions lead new sea lines of communication to competitive militarization. This is a simple question with serious implications. The potential for militarization depends, in part, on whether the key actors view the emerging sea lines of communication as a public, private, or club good. Economic theory offers a lens to examine potential militarization in the Arctic. This monograph uses a deductive case study approach to apply economic theory to the Arctic. Based on inductive reasoning this work makes recommendations for how to limit militarization, and if this cannot be achieved, how the United States should respond to militarization in the Arctic. This work concludes that when routes are viewed as public goods, they are unlikely to militarize. Militarization is likely to occur when routes are club good with disputed ownership, which is the current trajectory.